2020
DOI: 10.1523/jneurosci.1874-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Synchronize: Midfrontal Theta Dynamics during Rule Switching

Abstract: In recent years, several hierarchical extensions of well-known learning algorithms have been proposed. For example, when stimulus-action mappings vary across time or context, the brain may learn two or more stimulus-action mappings in separate modules, and additionally (at a hierarchically higher level) learn to appropriately switch between those modules. However, how the brain mechanistically coordinates neural communication to implement such hierarchical learning remains unknown. Therefore, the current study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(76 citation statements)
references
References 54 publications
(83 reference statements)
7
61
0
Order By: Relevance
“…First, it might suggest that top-down synchronization is exerted similarly towards both hemispheres independently of lateralization of stimuli and responses. This interpretation is consistent with a previous study testing the model prediction in a reversal rule learning task involving lateralized responses and reporting bilateral clusters of connectivity between FCz and posterior electrodes (Verbeke et al, 2020). Information on which networks are task-relevant and which should be inhibited could be coded in other aspects of the interactive dynamics between mPFC and posterior areas, such as phase coding or cross-frequency coupling (Helfrich and Knight, 2016), or by means of activity-silent and less resource consuming neurophysiological mechanisms (Stokes, 2015; Masse et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…First, it might suggest that top-down synchronization is exerted similarly towards both hemispheres independently of lateralization of stimuli and responses. This interpretation is consistent with a previous study testing the model prediction in a reversal rule learning task involving lateralized responses and reporting bilateral clusters of connectivity between FCz and posterior electrodes (Verbeke et al, 2020). Information on which networks are task-relevant and which should be inhibited could be coded in other aspects of the interactive dynamics between mPFC and posterior areas, such as phase coding or cross-frequency coupling (Helfrich and Knight, 2016), or by means of activity-silent and less resource consuming neurophysiological mechanisms (Stokes, 2015; Masse et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…According to the computational model proposed by Verguts (2017) and updated by his colleagues (Verbeke and Verguts, 2019; Senoussi et al, 2020b; Verbeke et al, 2020), theta oscillations from the mPFC control unit serve the purpose of synchronizing posterior task-relevant processing units. Therefore, we were primarily interested in investigating whether task-demands (i.e., preparing for implementation vs maintenance) affect connectivity between frontal and posterior areas.…”
Section: Methodsmentioning
confidence: 99%
“…Hebb’s favored mechanism for learning took the form of cell assemblies that become connected after being repeatedly activated at the same time. Modern investigations of this hypothesis in humans have confirmed that long-range synchronization between different brain regions is a reliable correlate of certain kinds of learning (Miltner, et al, 1999; Verbeke, et al, 2021). This coherence has often been found in the gamma band (Miltner, et al, 1999; Jutras, et al, 2009; Popescu, et al, 2009; Igarashi, et al, 2014), which is also associated with learning in our task (Figures 3, 6).…”
Section: Discussionmentioning
confidence: 97%
“…Also, the model included dummy regressors for the IPS-TMS stimulation and the PPC-TMS stimulation conditions and the interaction between each TMS stimulation condition and the task-related regressors. We explored frontal electrodes where theta activity related to prediction error has been described in prior work [20][21][22]30 . For both uPE regressors, we found a significant modulation (Figure 5).…”
Section: Parietal Inhibition Interrupts the Prediction Error Signal R...mentioning
confidence: 99%